Biology and Mechanics of Blood Flows Part II: Mechanics and Medical Aspects - Thiriet, Marc (CRM Series in Mathematical Physics,, 2008)
Biology and Mechanics of Blood Flows presents the basic knowledge and state-of-the-art techniques necessary to carry out investigations of the cardiovascular system using modeling and simulation. Part II of this two-volume sequence, Mechanics and Medical Aspects, refers to the extraction of input data at the macroscopic scale for modeling the cardiovascular system, and complements Part I, which focuses on nanoscopic and microscopic components and processes. This volume contains chapters on anatomy, physiology, continuum mechanics, as well as pathological changes in the vasculature walls including the heart and their treatments. Methods of numerical simulations are given and illustrated in particular by application to wall diseases. This authoritative book will appeal to any biologist, chemist, physicist, or applied mathematician interested in the functioning of the cardiovascular system.